2022
DOI: 10.5551/jat.63164
|View full text |Cite
|
Sign up to set email alerts
|

Association between Short-Term Blood Pressure Variability and Intracranial Atherosclerotic Plaque Vulnerability: A High-Resolution Magnetic Resonance Imaging Study

Abstract: Aim: short-term blood pressure variability (BPV) as a risk factor of atherosclerosis and cardiovascular events has been investigated. However, its association with atherosclerotic plaque vulnerability remains unknown. The objective of this study was to determine the association between short-term BPV and intracranial atherosclerotic plaque vulnerability.Methods: this is a cross-sectional analysis of 267 ischemic stroke patients with symptomatic intracranial atherosclerosis (mean age, 65±12 years old; 60.3% mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…As a result, chronic elevation of PP may lead to dysfunction of the blood-brain barrier, neurodegeneration, and dementia. Concerning cerebral arteries, another report suggested that 24-h blood pressure fluctuations in ischemic stroke patients are associated with intracranial intraplaque hemorrhage 24) . In our study, carotid artery plaque was noted to be thicker in the high-high group than in the low-low group (Tables 4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, chronic elevation of PP may lead to dysfunction of the blood-brain barrier, neurodegeneration, and dementia. Concerning cerebral arteries, another report suggested that 24-h blood pressure fluctuations in ischemic stroke patients are associated with intracranial intraplaque hemorrhage 24) . In our study, carotid artery plaque was noted to be thicker in the high-high group than in the low-low group (Tables 4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we do not rule out the hypothesis that intimal ICAC might mediate the association between BP and cerebral small vessel disease. It is possible that abnormal circadian BP rhythms, 24 morning surge, 25 or high 24-hour BP variability 26 would destabilize the atherosclerotic plaque localized in the intracranial carotid artery, leading to cerebrovascular complications. This is based on numerous studies implicating the association of these ambulatory BP indexes with carotid plaque presence and vulnerability, and with major cerebrovascular outcomes.…”
Section: Intracranial Arteriosclerosis Mediates the Association Betwe...mentioning
confidence: 99%
“…This is based on numerous studies implicating the association of these ambulatory BP indexes with carotid plaque presence and vulnerability, and with major cerebrovascular outcomes. [24][25][26] Future studies utilizing ambulatory BP and ICAC would provide novel insights regarding the physiopathology of cerebrovascular outcomes in relation to BP dysregulations.…”
Section: Intracranial Arteriosclerosis Mediates the Association Betwe...mentioning
confidence: 99%